The performance and response of additional passive auxiliary cooling system for safety of pressurized water nuclear reactors at unanticipated transients conditions - Ibrahim, Said. M. A.; Atia, Sami. I. (International Journal of Engineering and Technology, 2018)
The main function of nuclear safety of nuclear power reactors is to furnish assured removal of decay heat to an ultimate heat sink after safe shutdown of the reactor. Nuclear safety is the most challenging issue in nuclear energy; it is in fact of the utmost concern to all. Station Blackout (SBO) is one of the representative important accidents related to the electric power source in nuclear power plants. This research paper is concerned with thermal-hydraulic simulation of an additional secondary passive auxiliary feedwater system of a pressurized water reactor nuclear power plant (PWR NPP). The purpose is to analyze the performance, efficiency, and response of the behavior of the present additional secondary passive auxiliary feedwater system in case of a station blackout (SBO) unanticipated transients conditions. SBO could be one of the worst nuclear accidents. In this study, the thermal hydraulic analysis is performed by using RELAP thermal hydraulic code to develop a model of this PWR in the case of station blackout unanticipated transient conditions. The main conclusions of this study are that the additional secondary auxiliary passive feedwater safety system is adequate, efficient and effective as a heat sink to provide a reliable strong cooling capability of the secondary steam generator in the case of beyond design basic conditions. The newly added auxiliary cooling system affirms its capability to make an active contribution to the mitigation of the significant undesirable consequences during the station blackout accident. The presence of this cooling system is rather important for more safety assurance of nuclear reactors.
Keywords: Thermal-Hydraulic; RELAP Code; Nuclear safety; Station Blackout; PWR.